The pH- and freezing point values of milk in the Western and Southern Cape and factors affecting these values - Vassen, Peter (University of the Free State, 2003)
The milk yield per cow has gradually increased over the past two decades, and resulted in compositional changes of the milk that altered the physical properties of milk. pH a physical property, which is used as a rejection test on the milk receiving platform, is a resultant of the milk constituents and their concentrations. The current South African specification states that the pH of raw milk should fall within the limits, 6.60 and 6.75. Freezing point, a colligative property of milk, is depended on the concentration of solute ions in solution and not on the chemical identity of the solute. The measurement of the freezing point of milk provides the most reliable means of detecting and measuring extraneous water in milk. The current “accepted” South African specification states that the freezing point of raw milk should fall between -0.512 °C and -0.545°C. The specifications for pH and freezing point are at least 13 and 19 years old, respectively, and may be outdated, resulting in the rejection of acceptable milk or vice versa. The purpose of this study was therefore to determine if these specifications are still applicable or whether this topic warrants further research to establish new specifications. Seventeen variables as determined in 21 564 and 28 083 herd milk samples, originating in the Western Cape and the Tsitsikama regions of the Eastern cape of South Africa, were correlated with the pH- and freezing point values of raw cows’ milk, respectively. The pH-values obtained showed the following statistically characteristics, namely: mean (6.72), median (6.72), mode (6.70), and range (6.60 to 6.84). The corresponding statistics of the freezing point values were: mean (-0.523°C), median (-0.522°C), mode (-0.521°C), and range (-0.545 to -0.502°C). pH was significantly (p < 0.05) influenced by chloride (r = + 0.35), magnesium (r = + 0.21), calcium (r = - 0.20), average humidity (r = - 0.19), somatic cell count (r = + 0.16), average temperature (r = - 0.15), lactose (r = - 0.10), evaporation (r = - 0.09), fat (r = - 0.07), average rainfall (r = - 0.05), wind speed (r = + 0.04) and total bacterial count (r = -0.02), whereas protein, total solids, solids-non-fat, sunshine, and radiation showed no significant (p < 0.05) influence. Freezing point was significantly (p = 0.05) influenced by wind speed (r = + 0.36), lactose (r = + 0.35), solids-non-fat (r = - 0.35), protein (r = - 0.28), total solids (r = - 0.23), fat (r = - 0.20), somatic cell count (r = - 0.19), radiation (r = + 0.17), chloride (r = + 0.15), total bacterial count (r = - 0.14), average temperature (r = + 0.12), sunshine (r = + 0.06), evaporation (r = - 0.05) and average humidity (r = - 0.05), whereas calcium, magnesium, and rainfall showed no significant (p < 0.05) influence. Statistical analyses indicate that the pH was significantly (p < 0.05) influenced by region, season, breed, and feed and the freezing point by region, breed, feed, and not by season. The findings of this study justify the hypothesis that the pH specification, being ≥ 6.60 and ≤ 6.75, is outdated, because 14.2% of samples fell outside the upper limit. It would therefore appear that the freezing point standard is still valid because a small percentage, 1.88 %, of the samples studied, gave freezing points higher than the current specification, being ≤ -0.512°C. As samples drawn from bulk tanks might contain water residues, due to unintentional contamination, it may have contributed to the higher freezing points of these samples. The freezing point of an even smaller percentage, 1.28 %, of samples were found to be below the suggested lower limit.

Melkopbrengs per koei, as gevolg van beter genetika, voeding en bestuur, neem voortdurend toe. Produksietoenames gedurende die afgelope twee dekades was sodanige dat moontlike gepaadgaande verandering in melksamestelling die fisiese eienskappe van die melk kon beinvloed. pH is ‘n fisiese eienskap van melk wat deur die aanwesigheid en konsentrasie van verskeie melkbestandele daargestel word en word as ‘n aanvaardingstoets benut. Die huidige Suid-Afrikaanse pH-spesifikasie vir roumelk stel ‘n minimum en maksimum waarde van 6.60 en 6.75 onderskeidelik. Die vriespunt van melk word bepaal deur die gesamentlike konsentrasie van die molekule of ione en nie deur die chemise identiteit van die opgelosde stowwe nie. Die vriespuntsbepaling van melk verskaf is die mees betroubaarste metode vir die opsporing en meting van bygevoegde water in melk. Die huidige “aanvaarbare” Suid-Afrikaanse vriespuntspesifikasie vir roumelk is maksimum, -0.512°C, en minimum, -0.545°C. Die spesifikasies vir pH en vriespunt is onderskeidelik ten minste 13 en 19 jaar oud en mag dus as gevolg van tussentydse veranderinge in melksamestelling verouderd wees. Indien wel, kan dit tot gevolg hê dat aanvaarbare melk afgekeur word en andersom. Die doel van hierdie studie was om te bepaal of die pH- en vriespuntspesifikasies nog geldig is of aanpassing daarvan deur verdere studie ondersoek moet word. Sewentien veranderlikes, soos bepaal van 21 564 en 28 083 kuddemelkmonsters, afkomstig vanaf die Wes-kaap- en die Tsitsikama-streke van Suid-Afrika, is afsonderlik met die pH en vriespunt gekorrelleer. Die pH-waardes het die volgende statistiese eienskappe getoon, nl: gemiddelde (6.72), mediaan (6.72), modus (6.70), en verspreiding (6.60 tot 6.84). Die ooreenstemmende statistiek vir die vriespunte was as volg: gemiddelde (-0.523°C), mediaan (-0.522°C), modus (-0.521°C), en verspreiding (-0.545°C tot -0.502°C). pH was betekenisvol (p < 0.05) beïnvloed deur chloried (r = + 0.35), magnesium (r = + 0.21), kalsium (r = - 0.20), gemiddelde humiditeit (r = - 0.19), somatiese seltelling (r = + 0.16), gemiddelde temperatuur (r = - 0.15), laktose (r = - 0.10), verdamping (r = - 0.09), vet (r = - 0.07), reënval (r = - 0.05), windspoed (r = + 0.04) en bakteriese-telling (r = -0.02), terwyl proteien, totale vastestof, vetvrye vastestofinhoud, sonskyn, en bestraling geen betekenisvolle (p < 0.05) invloed getoon het nie. Vriespunt was betekenisvol (p < 0.05) beïnvloed deur die windspoed (r = + 0.36), laktose (r = + 0.35), vetvrye vastestofinhoud (r = - 0.35), proteïen (r = - 0.28), totale vastestof (r = - 0.23), vet (r = - 0.20), somatiese seltelling (r = - 0.19), bestraling (r = + 0.17), chloried (r = + 0.15), bakteriese-telling (r = - 0.14), gemiddelde temperatuur (r = + 0.12), sonskyn (r = + 0.06), verdamping (r = - 0.05) en gemiddelde humiditeit (r = - 0.05), terwyl kalsium, magnesium, en reënval geen betekenisvolle (p < 0.05) invloed getoon het nie. Statistiese ontledings toon dat die pH betekenisvol (p < 0.05) beïnvloed deur streek, seisoen, ras en voer en die vriespunt slegs deur die streek, ras en voer beïnvloed is. In die studie is gevind dat die pH in die geval van 14.2 % van die monsters hoër as die gespesifiseerde maksimum van 6.75 was. Die hipotese, dat die pH spesifikasies, nl., ≥ 6.60 and ≤ 6.75, dus verouderd is, word hierdeur bevestig. In die geval van die vriespunt, het slegs 1.88 % van die waardes die maksimum gespesifiseerde vriespunt van –0.512°C oorskrei. Hierdie persentasie moet beoordel word in die lig daarvan dat ‘n gedeelte van die monsters moontlik tydens produksie onopsetlik met water residu’s besoedel is. Slegs in 1.28 % van die monster is vriespunte van laer as –0.545°C gevind. Dit word dus afgelei dat die huidige vriespuntspesifikasie, ≤ -0.512°C en ≥ -0.545°C, nog geldig is.
Dissertation (M.Sc.Agric. (Food Science))--University of the Free State, 2003
Keywords: pH; Freezing point; Physical property; Colligative property; Specification; Milk -- Analysis; Milk -- Composition; Milk -- Freezing point